2016
DOI: 10.1002/ange.201508941
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Reduction of Low Concentrations of CO2 in a Porous Coordination Polymer with a Ruthenium(II)–CO Complex

Abstract: Direct use of low pressures of CO 2 as aC 1s ource without concentration from gas mixtures is of great interest from an energy-saving viewpoint. Porous heterogeneous catalysts containing both adsorption and catalytically active sites are promising candidates for such applications.H ere,w e report ap orous coordination polymer (PCP)-based catalyst, PCP-Ru II composite,b earing aR u II -CO complex active for CO 2 reduction. The PCP-Ru II composite showed improved CO 2 adsorption behavior at ambient temperature.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…At this time, heterogeneous MOF photocatalysts have been achieved by introducing photoactive catalytic sites (e.g., metal ions or metallolinkers) in MOF materials . Lin and co‐workers incorporated Re(bpydc)(CO) 3 Cl complexes into UiO‐67 to achieve a photocatalytic MOF for CO 2 reduction to carbon monoxide (CO) using a mix‐and‐match synthetic strategy .…”
Section: Electrocatalytic or Photochemical Reduction Of Co2mentioning
confidence: 99%
See 2 more Smart Citations
“…At this time, heterogeneous MOF photocatalysts have been achieved by introducing photoactive catalytic sites (e.g., metal ions or metallolinkers) in MOF materials . Lin and co‐workers incorporated Re(bpydc)(CO) 3 Cl complexes into UiO‐67 to achieve a photocatalytic MOF for CO 2 reduction to carbon monoxide (CO) using a mix‐and‐match synthetic strategy .…”
Section: Electrocatalytic or Photochemical Reduction Of Co2mentioning
confidence: 99%
“…Motivated by the above example, intensive research efforts have been made to explore and synthesize such heterogeneous MOF photocatalysts for visible‐light‐driven CO 2 reduction. Kajiwara and co‐workers introduced molecular catalyst (Ru 2+ (H 2 bpydc)(terpy)(CO))(PF 6 ) 2 or H 2 RuCO complex (ligand modified from (Ru 2+ (bpy)(terpy)(CO))(PF 6 ) 2 or Ru 2+ ‐CO) via post‐synthetic exchange into the UiO‐67 framework forming Zr‐bpdc/RuCO photocatalyst ( Figure a) . The resulting material exhibited high catalytic activity for CO 2 photoreduction to CO, HCOOH and H 2 .…”
Section: Electrocatalytic or Photochemical Reduction Of Co2mentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, metal-organic frameworks (MOFs), bene ting from their porous feature, ordered structure and molecular tunability, have been widely used to mediate photocatalytic CO 2 reduction. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In this eld, Lin et al, 16 incorporated Re(CO) 3 (bpy)Cl (bpy = bipyridine) modules into the UiO-67 framework, achieving a total turnover number (TON) of 10.9 in photocatalytic CO 2 -to-CO conversion. Wang et al achieved a high TON of 450 by using a Co-based zeolitic imidazolate framework as the cocatalyst in the presence of [Ru(bpy) 3 ] 2+ photosensitizer (PS).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that RuDCBPY‐doped UiO‐67 could be grown onto the glass substrates coated with the conductive fluorine‐doped tin oxide (FTO) without changing the excited state properties of the material . Before long, RuDCBPY‐doped UiO‐67 films were studied to grow onto TiO 2 and in order to generate a sensitizing material for photovoltaic solar cell applications in the report of Maza et al . The synthetic MOFs sensitized solar cells could generate a moderate photocurrent in response to the 1 sun illumination which was simulated.…”
Section: Uio‐67 Derivativesmentioning
confidence: 99%